Assessing the clinical outcome of nab‐paclitaxel in Chinese patients with advanced non‐small‐cell lung cancer. (20th October 2015) - Zeng, Junli; Yin, Jie; Yuan, Dongmei; Yang, Wen; Liang, Wenjun; Wu, Guannan; Song, Yong
Abstract: Purpose: Nab‐paclitaxel [nab‐P, 130‐nm albumin‐bound paclitaxel particles] is a new solvent‐free paclitaxel that allows for high intratumoral concentration and has been approved for use in various solid tumours. The aim of our study was to evaluate the efficacy and safety of nab‐paclitaxel in the treatment of advanced non‐small‐cell lung cancer [NSCLC]. Patients and Methods: We assessed 101 Chinese patients who were diagnosed with Stage IIIB or IV NSCLC from August 2009 to November 2014.The patients were injected with nab‐paclitaxel [260 mg/m 2, day1] with or without platinum. Patients who completed more than two treatment cycles were assessed for response and survival. All patients were assessed for adverse events. Results: The efficacy was evaluated in 79 patients; the overall response rate was 32.9%, and the disease control rate was 89.9%. Subgroup analysis found patients with squamous cell carcinoma, and combination therapies showed better outcomes. The median progression‐free survival was 5.3 months [95%CI: 4.6–5.9], and the median overall survival was 8.9 months [95%CI: 6.1–11.6]. The main grades 3/4 adverse events were peripheral neuropathy [5.9%], leukopenia [5.0%], and anaemia [3.0%]. Additionally, severe abnormal hepatic function [2.0%], alopecia [2.0%], thrombocytopenia [1.0%] and fatigue [1.0%] could also be identified in some patients. Conclusion: The nab‐paclitaxel chemotherapy could achieve significant tumour responses and encourage survival in advanced NSCLC patients with tolerable toxicities. Further clinical studies are needed to explore the optimal therapy regimen and target users.